WTP 19aalnxx: Discovery of a Bright Mid-infrared Transient in the Emerging Class of Low-luminosity Supernovae Revealed by Delayed Circumstellar Interaction - Charlotte Myers; Kishalay De; Lin Yan; Jacob E. Jencson; Nicholas Earley; Christoffer Fremling; Daichi Hiramatsu; Mansi M. Kasliwal; Ryan M. Lau; Morgan MacLeod; Megan Masterson; Christos Panagiotou; et al. (The Astrophysical Journal)
While core-collapse supernovae (SNe) often show early and consistent signs of circumstellar medium (CSM) interaction, some exhibit delayed signatures due to interaction with distant material around the progenitor star. Here we present the discovery in NEOWISE data of WTP 19aalnxx, a luminous mid-infrared (MIR) transient in the outskirts of the galaxy KUG 0022-007 at ≈190 Mpc. First detected in 2018, WTP 19aalnxx reaches a peak absolute (Vega) magnitude of ≈−22 at 4.6 μ m in ≈3 yr, comparable to the most luminous interacting SNe. Archival data reveal a ≳5× fainter optical counterpart detected since 2015, while follow-up near-infrared observations in 2022 reveal an extremely red ( Ks − W2 ≈ 3.7 mag) active transient. Deep optical spectroscopy confirm strong CSM interaction signatures via intermediate-width Balmer emission lines and coronal metal lines. Modeling the broadband spectral energy distribution, we estimate the presence of ≳10 ^−2 M _⊙ of warm dust, likely formed in the cold dense shell. Together with the lack of nebular Fe emission, we suggest that WTP 19aalnxx is a missed, low (optical) luminosity SN in an emerging family of core-collapse SNe distinguished by their CSM-interaction-powered MIR emission that outshines the optical bands. Investigating the Zwicky Transient Facility sample of SNe with NEOWISE data, we find 16 core-collapse SNe (≳3% in a volume-limited sample) without early signs of CSM interaction that exhibit delayed IR brightening, suggestive of dense CSM shells at ≲10 ^17 cm. We suggest that synoptic IR surveys offer a new route to revealing late-time CSM interaction and the prevalence of intense terminal mass loss in massive stars.